Induction of Development as Determined by a Chemical Criterion : Part II - J. Karrer; W.F. Berg (CHIMIA)
In earlier papers we reported that we could not find any induction period in a monodisperse liquid AgBr emulsion, using a uniform exposure and a locus- and orientation independent development. This applied to only one system: a pure AgBr emulsion in a simple hydroquinone developer containing no bromide ions (pH 12.1). In an attempt to obtain data which would allow us to generalize this finding we repeated this experiment first with a AgBrI-emuIsion, containing 4 Mol-% iodide, secondly with a hydroquinone developer containing KBr (10-3N), and obtained essentially the same results.